Ancestry, blood, and heredity. Attitudes towards biological descent in late medieval Tuscany, c.1250-1400 - Andrés Porras (2022)
This thesis examines intellectual and social attitudes to biological descent in late medieval Tuscany. In recent decades, historians have paid increasing attention to the body as a locus of experience, individuality, and identity. Yet bodies, like individuals, always have a genealogy. Thus, in this thesis, I set out to explore how ideas of biological descent shaped medieval understandings of the body and the significance of biological ties. First, I argue that medieval society developed a proto-materialistic approach to human personality that highlighted the role of hereditary physiological principles in the interpretation of character and behaviour. As a result, biological ancestry and blood emerged at the centre of individual and group identities. Subsequent chapters explore thinking about biological descent in the family, social units like the nobility, and political communities. A final chapter explores the diffusion of theories of natural love and demonstrates how similar patterns of thinking about biological descent can be identified across different dimensions of social life. In this thesis, intellectual and literary sources delineate the framework of ideas, beliefs, and values which informed attitudes to biological descent. On the other hand, normative and documentary sources illustrate how ideas of biological descent informed, and were informed by, social, legal, and political practices and structures. In this manner, biological descent emerges as a valuable category for the analysis of social relationships, offering fresh insights into a number of intertwined historiographical areas of concern. My study reveals that against dualist conceptions of human personhood, late medieval society held that human beings ‘were’ rather than ‘possessed’ bodies. As a result, the body and descent were perceived to be imbued with meaning and a source of normative values. Ultimately, this thesis lends support to the idea that late medieval society recovered nature as an ordering principle of society.